Method for improving strength of nano silicon dioxide sol grouting material

By mixing small-particle spherical nanosilica sol with chain nanosilica sol, surface modification and adding vapor phase silica to form a nanosilica sol grout with high gel strength, the problem of insufficient strength of the existing grout material is solved, and high compressive strength and low viscosity are achieved.

CN119797378APending Publication Date: 2025-04-11CNPC BOHAI DRILLING ENG +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311312694.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing nano silica sol grouting materials have low strength and are difficult to meet the needs of high compressive strength.

Method used

The small-particle spherical nanosilica sol and the chain nanosilica sol are mixed in proportion, and PVP is added at 50-80°C for surface modification, followed by adding vapor phase silica powder under high-speed stirring, and finally a gel agent and an acidity regulator are added to form a mixed liquid with high gel strength.

Benefits of technology

By forming a Si-O-Si inorganic mesh structure, the gel strength of the nano-silica sol grout is significantly improved, so that it can better meet the needs of high compressive strength while maintaining low viscosity and good filling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004488359370000071
    Figure BDA0004488359370000071
Patent Text Reader

Abstract

The invention relates to the technical field of chemical grouting materials, in particular to a method for improving the strength of a nano silicon dioxide sol grouting material, which comprises the following steps: mixing small-particle-size spherical nano silicon dioxide sol and chain-shaped nano silicon dioxide sol in proportion, modifying the surface of the nano silicon dioxide sol by using polyvinylpyrrolidone, and preparing the nano silicon dioxide sol grouting material. The preparation method comprises the following steps: preparing PVP-modified nano-silica sol, slowly adding fumed silica into the PVP-modified nano-silica sol under high-speed stirring to obtain a uniformly dispersed mixed solution, and finally adding a gelling agent and an acidity regulator to form a coherent siloxane bond network on Si-OH on the surfaces of the nano-silica sol and the fumed silica so as to prepare the PVP-modified nano-silica gel. A liquid is converted into a gelatinous solid; the grouting material which is high in strength, low in viscosity, good in groutability and small in environmental pollution is invented by taking the spherical nano silicon dioxide sol as a main agent and specifically adding the chain-shaped nano silicon dioxide sol and the fumed silica.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical grouting materials, in particular to a method for improving the strength of nano silicon dioxide sol grouting material. Background Art

[0002] Grouting is a common method to improve the strength and impermeability of rock and soil, and has been widely used in tunnels, dams, mines, deep oil wells and other fields. Cement-based grouting materials have the advantages of high strength and low cost, but due to their particle size, it is difficult to meet the construction requirements when treating fine cracks or pores. At present, better penetration and plugging strength can be achieved through chemical grouting. Invention patent CN103030967B discloses a polyurethane grouting material with isocyanate compounds and polyether polyols as main raw materials; invention patent CN104628994B discloses a fully permeable epoxy grouting material with acetone, furfural and epoxy resin as main raw materials; although there is a lot of experience in using organic molecule-based grouting materials in controlling viscosity, achieving the required penetration length, the required gel time, and well plugging small cracks or holes, it also brings huge toxicity and environmental damage.

[0003] Nano silica sol is a nano silica aqueous dispersion, and the gel formed is composed of silica and silicate, which is non-toxic and has no environmental pollution. At the same time, silica sol has a small particle size and low viscosity, and can easily penetrate the porous matrix of the stratum to block smaller pores. Importantly, there are abundant Si-OH structures on the surface of silica sol, and Si-O-Si covalent bonds can be formed between the particles by controlling the addition of gelling agent, thereby forming a gel with a certain strength within a specified time. Invention patent CN109305777B discloses a grouting material with silica sol as the main raw material, with low initial viscosity and controllable gel time. However, the gel strength is low and the morphology and particle size of silica sol are not described. Therefore, silica sol has the problem of insufficient compressive strength as a grouting material. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the strength of nano-silica sol grouting material to solve the problem of the strength of existing silica sol grouting material.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] A method for improving the strength of nano-silica sol grouting material comprises the following steps:

[0007] Step 1: Mix small-particle spherical nano-silica sol and chain-shaped nano-silica sol in proportion;

[0008] Step 2: Add PVP to the nano-silica sol prepared in step 1 at 50-80°C, and continue stirring for 0.5-3h to modify the surface of the nano-silica sol;

[0009] Step 3: Slowly add the fumed silica powder to the nano-silica sol prepared in step 2 under high-speed stirring at 2000-5000 rpm, and continue to stir at high speed for 1-3 hours to mix evenly;

[0010] Step 4: Add a certain amount of gelling agent and acidity regulator to the nano-silica sol-fumed silica mixture prepared in step 3 to form a gel within a certain period of time.

[0011] Furthermore,

[0012] In step 1, the particle size of the small-particle spherical nano-silica sol is 5-20 nm.

[0013] Furthermore,

[0014] In step 1, the aspect ratio of the chain-like nano-silica sol is 2-8.

[0015] Furthermore,

[0016] The solid content of the small-particle spherical nano-silica sol is 20-40%;

[0017] The solid content of the chain-shaped nano-silicon dioxide sol is 20-40%.

[0018] Furthermore,

[0019] In step 1, the mass ratio of the chain-shaped nano-silica sol to the small-particle spherical nano-silica sol is 1:(1-9).

[0020] Furthermore,

[0021] In step 2, the molecular weight of the PVP is K17-K90, and the concentration of the PVP is 0.05-0.2 mol / L.

[0022] Furthermore,

[0023] In step 3, the mass ratio of the fumed silica to the silica sol is 1:(25-100).

[0024] Furthermore,

[0025] In step 4, the gelling agent is at least one of potassium chloride, sodium chloride, potassium sulfate, sodium silicate, and potassium carbonate.

[0026] Furthermore,

[0027] In step 4, the acidity regulator is at least one of hydrochloric acid, acetic acid, sodium bicarbonate, and phosphoric acid.

[0028] Furthermore,

[0029] The method comprises the following steps:

[0030] Step 1: Mix 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 45 g of 5 nm spherical nano-silica sol with a solid content of 40%.

[0031] Step 2: At 50°C, add 1 mL of 0.05 mol / L PVP K30 solution to the silica sol in step 1 and continue stirring for 1 h to modify the surface of the nano-silica sol;

[0032] Step 3: Under high-speed stirring at 5000 rpm, add 2 g of fumed silica powder to the solution in step 2 within 40 minutes, and continue stirring for 2 hours after the addition;

[0033] Step 4: Add 8 g of 10% KCl solution to the nano-silica sol-fumed silica mixture prepared in step 3, and adjust the pH to 7 with 2% HCl solution to form a gel within a certain period of time.

[0034] Based on the above technical solutions, the technical effects that can be achieved by the present invention are:

[0035] The method comprises mixing a small-particle spherical nano-silica sol and a chain-shaped nano-silica sol in proportion, modifying the surface of the nano-silica sol with polyvinyl pyrrolidone (PVP), slowly adding fumed silica into the nano-silica sol modified with PVP under high-speed stirring to obtain a uniformly dispersed mixed solution, and finally adding a gelling agent and an acidity regulator to form a coherent siloxane bond (Si-O-Si) network between the nano-silica sol and the Si-OH on the surface of the fumed silica, thereby converting the liquid into a gel-like solid. In the method, the chain-shaped nano-silica can fill the gap when the spherical silica and the fumed silica particles are combined, so that the arrangement between the particles is more compact. More importantly, a large number of silanol groups (Si-OH) are present on the surface of the hydrophilic fumed silica, which can be combined with the Si-OH on the surface of the silica sol to form a Si-O-Si inorganic network structure, thereby greatly improving the gel strength. DETAILED DESCRIPTION

[0036] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0037] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0038] Therefore, the following detailed description is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] (1) 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 45 g of 5 nm spherical nano-silica sol with a solid content of 40% were mixed.

[0041] (2) At 50° C., 1 mL of 0.05 mol / L PVP K30 solution was added to the silica sol prepared in step (1), and the mixture was stirred for 1 h to modify the surface of the nano-silica sol;

[0042] (3) Under high-speed stirring at 5000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0043] (4) Add 8 g of 10% KCl solution to the nano-silica sol-fumed silica mixture prepared in step (3), and adjust the pH to 7 with 2% HCl solution to form a gel within a certain period of time; use a universal material testing machine to measure the strength of the gel, using a cylindrical flat-head punch with a diameter of 12.7 mm; punching speed: 0.5 mm / s; punching depth: 20 mm; the sample is made The cylinder was pressed to 20 mm and the force required to break the gel was recorded as 394.10 N.

[0044] Example 2

[0045] (1) 10 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 40 g of 5 nm spherical nano-silica sol with a solid content of 40% were mixed.

[0046] (2) At 50° C., 1 mL of 0.05 mol / L PVP K30 solution was added to the silica sol prepared in step (1), and the mixture was stirred for 1 h to modify the surface of the nano-silica sol;

[0047] (3) Under high-speed stirring at 5000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0048] (4) Add 8 g of 10% KCl solution to the nano-silica sol-fumed silica mixture prepared in step (3), and adjust the pH to 7 with 2% HCl solution to form a gel within a certain period of time; and use the same test conditions as in Example 1, and record the force required for the gel to break as 376.45 N.

[0049] Example 3

[0050] (1) 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 2 and 45 g of 20 nm spherical nano-silica sol with a solid content of 40% were mixed.

[0051] (2) At 50° C., 1 mL of 0.05 mol / L PVP K30 solution was added to the silica sol prepared in step (1), and the mixture was stirred for 1 h to modify the surface of the nano-silica sol;

[0052] (3) Under high-speed stirring at 5000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0053] (4) 8 g of 10% KCl solution was added to the nano-silica sol-fumed silica mixture prepared in step (3), and the pH was adjusted to 7 with 2% HCl solution to form a gel within a certain period of time; and the same test conditions as in Example 1 were used, and the force required for the gel to break was recorded as 208.83 N.

[0054] Example 4

[0055] (1) 25 g of chain-shaped nano-silica sol with a solid content of 20% and an aspect ratio of 8 and 25 g of 5 nm spherical nano-silica sol with a solid content of 20% were mixed.

[0056] (2) At 50° C., 1 mL of 0.05 mol / L PVP K30 solution was added to the silica sol prepared in step (1), and the mixture was stirred for 1 h to modify the surface of the nano-silica sol;

[0057] (3) Under high-speed stirring at 5000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0058] (4) Add 8 g of 10% NaCl solution to the nano-silica sol-fumed silica mixture prepared in step (3), and adjust the pH to 7 with 5% acetic acid solution to form a gel within a certain period of time; and use the same test conditions as in Example 1, and record the force required for the gel to break as 198.35 N.

[0059] Example 5

[0060] (1) 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 45 g of 5 nm spherical nano-silica sol with a solid content of 40% were mixed.

[0061] (2) adding 1 mL of 0.2 mol / L PVP K17 solution to the silica sol in step (1) at 50° C. and continuing stirring for 1 h to modify the surface of the nano-silica sol;

[0062] (3) Under high-speed stirring at 5000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0063] (4) 8 g of 10% KCl solution was added to the nano-silica sol-fumed silica mixture prepared in step (3), and the pH was adjusted to 7 with 2% HCl solution to form a gel within a certain period of time; and the same test conditions as in Example 1 were used, and the force required for the gel to break was recorded as 369.63 N.

[0064] Example 6

[0065] (1) 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 45 g of 5 nm spherical nano-silica sol with a solid content of 40% were mixed.

[0066] (2) adding 1 mL of 0.05 mol / L PVP K90 solution to the silica sol in step (1) at 80° C. and continuing stirring for 1 h to modify the surface of the nano-silica sol;

[0067] (3) Under high-speed stirring at 2000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0068] (4) Add 8 g of 10% KCl solution to the nano-silica sol-fumed silica mixture prepared in step (3), and adjust the pH to 7 with 2% HCl solution to form a gel within a certain period of time; and use the same test conditions as in Example 1, and record the force required for the gel to break as 241.75 N.

[0069] The preparation method of Example 7-9 is the same as that of Example 1, except that the amount of fumed silica added in step (3) is different. The following table (Table 1) shows the amount of fumed silica added in step (3) of Example 7-9 and the force required for gel rupture.

[0070] Table 1 Amount of fumed silica added in Examples 7-9 and the force required for gel rupture

[0071] Comparative Example 1

[0072] (1) Take 50 g of 5 nm spherical nano-silica sol with a solid content of 40%.

[0073] (2) At 50° C., 1 mL of 0.05 mol / L PVP K30 solution was added to the silica sol prepared in step (1), and the mixture was stirred for 1 h to modify the surface of the nano-silica sol;

[0074] (3) Under high-speed stirring at 5000 rpm, 2 g of fumed silica powder was added to the solution of step (2) within 40 min, and stirring was continued for 2 h after the addition;

[0075] (4) Add 8 g of 10% KCl solution to the nano-silica sol-fumed silica mixture prepared in step (3), and adjust the pH to 7 with 2% HCl solution to form a gel within a certain period of time; and use the same test conditions as in Example 1, and record the force required for the gel to break as 75.62 N.

[0076] Comparative Example 2

[0077] (1) 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 45 g of 5 nm spherical nano-silica sol with a solid content of 40% were mixed.

[0078] (2) At 50° C., 1 mL of 0.05 mol / L PVP K30 solution was added to the silica sol prepared in step (1), and the mixture was stirred for 1 h to modify the surface of the nano-silica sol;

[0079] (3) 8 g of 10% KCl solution was added to the nano-silica sol prepared in step (3), and the pH was adjusted to 7 with 2% HCl solution to form a gel within a certain period of time; and the same test conditions as in Example 1 were used, and the force required for the gel to break was recorded as 160.58 N.

[0080] Comparative Example 3

[0081] (1) Take 50 g of 5 nm spherical nano-silica sol with a solid content of 40%.

[0082] (2) 8 g of 10% KCl solution was added to the nano-silica sol prepared in step (1), and the pH was adjusted to 7 with 2% HCl solution to form a gel within a certain period of time; and the same test conditions as in Example 1 were used, and the force required for the gel to break was recorded to be 36.85 N.

[0083] From the data of Examples 1-9 and Comparative Examples 1-3, it can be seen that the grouting material prepared by the method for improving the strength of nano-silica sol grouting material provided in this embodiment has a gel breakage force greater than the gel breakage force of the comparative example. This embodiment uses spherical nano-silica sol as the main agent, specifically adds chain nano-silica sol and fumed silica, and invents a grouting material with high strength, low viscosity, good groutability, and low environmental pollution. The hydrophilic fumed silica surface has a large number of silanol groups (Si-OH), which can be combined with Si-OH on the surface of silica sol to form a Si-O-Si inorganic network structure, which greatly improves its gel strength. More importantly, the addition of chain nano-silica can fill the gap when the spherical silica and fumed silica particles are combined, so that the arrangement between the particles is more compact, and the gel strength is further improved.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for improving the strength of nano-silica sol grouting material, characterized in that: The following steps are involved: Step 1: Mix small-particle spherical nano-silica sol and chain-shaped nano-silica sol in proportion; Step 2: Add PVP to the nano-silica sol prepared in step 1 at 50-80°C, and continue stirring for 0.5-3h to modify the surface of the nano-silica sol; Step 3: Slowly add the fumed silica powder to the nano-silica sol prepared in step 2 under high-speed stirring at 2000-5000 rpm, and continue to stir at high speed for 1-3 hours to mix evenly; Step 4: Add a certain amount of gelling agent and acidity regulator to the nano-silica sol-fumed silica mixture prepared in step 3 to form a gel within a certain period of time.

2. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 1, the particle size of the small-particle spherical nano-silica sol is 5-20 nm.

3. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 1, the aspect ratio of the chain-like nano-silica sol is 2-8.

4. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: The solid content of the small-particle spherical nano-silica sol is 20-40%; The solid content of the chain-shaped nano-silicon dioxide sol is 20-40%.

5. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 1, the mass ratio of the chain-shaped nano-silica sol to the small-particle spherical nano-silica sol is 1:(1-9).

6. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 2, the molecular weight of the PVP is K17-K90, and the concentration of the PVP is 0.05-0.2 mol / L.

7. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 3, the mass ratio of the fumed silica to the silica sol is 1:(25-100).

8. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 4, the gelling agent is at least one of potassium chloride, sodium chloride, potassium sulfate, sodium silicate, and potassium carbonate.

9. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: In step 4, the acidity regulator is at least one of hydrochloric acid, acetic acid, sodium bicarbonate, and phosphoric acid.

10. The method for improving the strength of nano-silica sol grouting material according to claim 1, characterized in that: The following steps are involved: Step 1: Mix 5 g of chain-shaped nano-silica sol with a solid content of 30% and an aspect ratio of 8 and 45 g of 5 nm spherical nano-silica sol with a solid content of 40%; Step 2: At 50°C, add 1 mL of 0.05 mol / L PVP K30 solution to the silica sol in step 1 and continue stirring for 1 h to modify the surface of the nano-silica sol; Step 3: Under high-speed stirring at 5000 rpm, add 2 g of fumed silica powder to the solution in step 2 within 40 minutes, and continue stirring for 2 hours after the addition; Step 4: Add 8 g of 10% KCl solution to the nano-silica sol-fumed silica mixture prepared in step 3, and adjust the pH to 7 with 2% HCl solution to form a gel within a certain period of time.

Citation Information

Patent Citations

  • Polyurethane grouting material

    CN103030967B

  • A fully permeable mutant grouting material

    CN104628994B

  • Silica sol grouting materials, their preparation methods and applications

    CN109305777B